The relevance of gene flow with wild relatives in understanding the domestication process - Alejandra Moreno-Letelier; Jonás A. Aguirre-Liguori; Daniel Piñero; Alejandra Vázquez-Lobo; Luis E. Eguiarte (Royal Society Open Science, 2020)
The widespread use of genomic tools has allowed for a deeper understanding of the genetics and the evolutionary dynamics of domestication. Recent studies have suggested that multiple domestications and introgression are more common than previously thought. However, the ability to correctly infer the many aspects of domestication process depends on having an adequate representation of wild relatives. Cultivated maize (Zea mays ssp. mays) is one of the most important crops in the world, with a long and a relatively well-documented history of domestication. The current consensus points towards a single domestication event from teosinte Zea mays ssp. parviglumis from the Balsas Basin in Southwestern Mexico. However, the underlying diversity of teosintes from Z. mays ssp. parviglumis and Zea mays ssp. mexicana was not taken into account in early studies. We used 32 739 single nucleotide polymorphisms (SNPs) obtained from 29 teosinte populations and 43 maize landraces to explore the relationship between wild and cultivated members of Zea. We then inferred the levels of gene flow among teosinte populations and maize, the degree of population structure of Zea mays subspecies, and the potential domestication location of maize. We confirmed a strong geographic structure within Z. mays ssp. parviglumis and documented multiple gene flow events with other members of the genus, including an event between Z. mays ssp. mexicana and maize. Our results suggest that the likely ancestor of maize may have been domesticated in Jalisco or in the southern Pacific Coast and not in the Balsas Basin as previously thought. In this context, different populations of both teosinte subspecies have contributed to modern maize's gene pool. Our results point towards a long period of domestication marked by gene flow with wild relatives, confirming domestication as long and ongoing process.